Preparation and Characterization of UV-Curable, Boron-Containing, Transparent Hybrid Coatings - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY, 2011)
A series of ultraviolet (UV)-curable, boron-containing hybrid coatings were prepared by an anhydrous sol-gel technique from a mixture of an acrylated bisphenol A based epoxy resin, methacryloxymethyl triethoxysilane, and boric acid. The use of boric acid allowed the hydrolysis and condensation of hybrid silicon alkoxides without the further addition of water or a catalyst. The chemical structure of the boron-containing hybrid coatings was characterized with Fourier transform infrared, real-time infrared, and Si-29 cross-polarization/magic-angle spinning NMR techniques. UV-curable coatings were applied to polycarbonate and Plexiglas substrates. The physical and mechanical properties of the UV-cured coatings (e.g., pendulum hardness, pencil hardness, con-tact angle, gel content, methyl ethyl ketone rubbing test, tensile test, abrasion resistance, chemical resistance, neutron absorption, and limiting oxygen index) were examined. The hybrid coatings showed a significant enhancement in their radiation-shielding properties. The thermal behavior of the coatings was also evaluated. It was observed that the thermal stability of the coatings mainly depended on their boron and silicate contents. The results of all analyses of the free films and coatings were examined. VC 2010 Wiley Periodicals, (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 2112-2121, 2011
Keywords: coatings; crosslinking; flame retardance; irradiation; neutron reflectivity; FLAME-RETARDANT THERMOSETS; SOL-GEL PROCESS; BISPHENOL; OLIGOMERS; ACRYLATE; POLYMER; RESINS; ACID